Analisis Makna Perjamuan Kudus Anak bagi Pemahaman Orang Tua di Gereja Toraja Jemaat Gasing - Hardi Saputra; Karnia Melda B; Roby Marrung; Gilber Awaeh; Ronaldo Stefanus (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
The Holy Communion is one of the sacraments performed in the Toraja Church as a direct command from God for all who believe in Jesus Christ. Therefore, everyone, both adults and children, is required to participate as part of the Kingdom of God's family. This study aims to analyze parents' understanding of the practice of Holy Communion involving children in the Gasing Congregation of the Toraja Church. The research employs a qualitative approach with a descriptive method to explain parents' understanding of the meaning and practice of Holy Communion involving children. Data collection was conducted through in-depth interviews, field observation, and relevant literature review related to the research topic. The findings indicate that many parents still lack a proper understanding of the theological significance of Holy Communion, particularly when it involves children. Most parents simply follow the synod's decision without deeply understanding its theological foundation. Moreover, the church does not provide direct pastoral guidance to parents but merely reads out the meaning of Holy Communion during Sunday worship services, resulting in very limited comprehension among the congregation. Therefore, more intensive socialization and guidance from the church council to all congregation members, especially parents, is highly needed. This research is expected to contribute to the development of knowledge at IAKN Toraja and provide insights for readers, particularly congregants of the Toraja Church in general.